Developing Learning Media Based on PowToon Application for Teaching English for Nurses - Putu Rusanti; Kadek Maya Cyntia Dewi (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2021)
This research aimed to identify the need analysis of learning English for Nurses (EFN) for nursing students and to develop learning media by using powtoon application in teaching English for Nurses. The research employed research and development (R&D) design. It was used Sugiyono model consisted of potential and problem, data collection, product design, design validation, design revision, product testing, product revision, and massive production. The data were collected through questionnaires and interview. The learning videos were validated by expert judges and were also done field testing to the 42 nursing students. The data were analyzed descriptively qualitative. The result of the research showed that 1) 64.5% of the students would like to combine the material between general English and specific topics about nursing, 2) The developed learning video consisted of some parts such as opening, learning objectives, content, conversation, vocabularies, and closing. The result of expert judges both in media and material were 87.5% and 93.5% which were categorized as excellent materials. It is expected that the learning video can be applied in teaching and learning process.